2022
DOI: 10.1080/19490976.2022.2104089
|View full text |Cite
|
Sign up to set email alerts
|

Gut dysbiosis impairs hippocampal plasticity and behaviors by remodeling serum metabolome

Abstract: Accumulating evidence suggests that gut microbiota as a critical mediator of gut-brain axis plays an important role in human health. Altered gut microbial profiles have been implicated in increasing the vulnerability of psychiatric disorders, such as autism, depression, and schizophrenia. However, the cellular and molecular mechanisms underlying the association remain unknown. Here, we modified the gut microbiome with antibiotics in newborn mice, and found that gut microbial alteration induced behavioral impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 85 publications
0
25
0
Order By: Relevance
“…This low-grade systemic inflammation is known as metabolic endotoxemia and can lead to several chronic inflammatory conditions [ 229 ]. Fructose-induced dysbiosis-triggered hippocampal neuroinflammation and neuronal loss in mice may highlight a potential mechanism for the neurological and psychiatric impairments associated with sugar and obesity [ 224 , 228 , 233 ].…”
Section: Possible Mechanisms Of Actionmentioning
confidence: 99%
“…This low-grade systemic inflammation is known as metabolic endotoxemia and can lead to several chronic inflammatory conditions [ 229 ]. Fructose-induced dysbiosis-triggered hippocampal neuroinflammation and neuronal loss in mice may highlight a potential mechanism for the neurological and psychiatric impairments associated with sugar and obesity [ 224 , 228 , 233 ].…”
Section: Possible Mechanisms Of Actionmentioning
confidence: 99%
“…The microbiome is necessary for the normal development of hippocampal and microglial cell morphology ( Luczynski et al, 2016 ). Recently, Liu et al observed microbiome deficiency altered dendritic signaling integration in the Cornu Ammonis1 region of mice ( Liu et al, 2022 ). The presence of activated microglia and reactive astrocytes in the vicinity of amyloid plaques is characteristic of AD neuroinflammation, mainly in the hippocampus ( Crews and Masliah, 2010 ; Cattaneo et al, 2017 ).…”
Section: Crosstalk Between the Peripheral And Central Systems And Alt...mentioning
confidence: 99%
“…In line with these findings, intra-species FMT (5xFAD to WT mice) reduced the survival and proliferation of neurons (Kim et al, 2021), and the recruitment and dendritic complexity of immature neurons was deficient in a familial AD mouse model (Mishra et al, 2022). Interestingly, recent studies have shown that that transfer of a WT mouse microbiome into APPswe/PSEN1dE9 mice improved spatial memory and synaptic plasticity (Sun et al, 2019), that reconstitution with normal gut flora in newborn mice protected against decreased AHN and cognitive deficits in antibiotic-treated mice (Liu et al, 2022), and that augmentation of AHN restored the dendritic development of new neurons, coupled with an enhancement of spatial recognition memory (Mishra et al, 2022). Thus, future studies should address whether the changes we observed in adult rats that received FMT from AD human donors are reversible, as well as mechanistic pathways that connect the gut microbiome to AHN.…”
Section: Discussionmentioning
confidence: 99%